A Case of Delayed Neurological Recovery with Luxury Perfusion and a High Intracranial Arterial Calcification Burden - Suh, Hong-Il; Lee, Seon-Wook; Eom, Young-In; Lee, Jin Soo (Journal of stroke, 2014)
KCI Citation Count: 2